The patient safety competency self-evaluation tool for nursing students: A validity and reliability study - Antia Antia (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Nurses must pay attention to patient safety. The quality of learning in nursing students must be improved with valid and reliable instruments to evaluate safety knowledge, skills, and behaviors regarding patient safety. Purpose: To determine the validity and reliability of the patient safety self-evaluation instrument, which was developed to evaluate patient safety in nursing students. Method: The research design used an observational research type with a methodological study approach to determine the validity and reliability of Patient Safety Competency Self-Evaluation (PSCSE) instrument. The study took place from March to June 2024, Esa Unggul University, Jakarta. Using purposive sampling and the Slovin formula, 71 participants were selected, who met specific inclusion and exclusion criteria. Univariate statistical analysis was conducted, including used Pearson correlation and the reliability test used Cronbach alpha with a significance level of 0.05. Results: The results of the validity test using Pearson Product moment on 6 knowledge questions with a value of (r= 0.281-0.568), 21 items of questions about skills (r= 0.422-0.806), 13 behavioral items (r= 0.273-0.789). Cronbach alpha (0.950) so that this instrument item is valid and reliable at a significant level of 0.05. Conclusion: The patient safety self-evaluation instrument has met the validity and reliability criteria for measuring knowledge, skills and attitudes in nursing students.